Diet and asthma in Dutch school children (ISAAC-2). Issue 12 (21st October 2005) - Tabak, C; Wijga, A H; de Meer, G; Janssen, N A H; Brunekreef, B; Smit, H A
Abstract : Background: The rise in the prevalence of asthma in western societies may be related to changed dietary habits. Epidemiological studies in children have shown inverse associations of asthma related outcomes with intake of fruits, vegetables, dairy and whole grain products, and fish. In contrast to most previous studies, we used both questionnaire and clinical data to define asthma. Methods: Intake of the abovementioned foods was studied in relation to asthma in 598 Dutch children aged 8–13 years. Dietary intake was estimated using a parent completed semi-quantitative food frequency questionnaire. Current wheeze and current asthma were defined based on questionnaire data. More complex end points were defined using information on bronchial hyperresponsiveness (BHR) and atopic sensitisation as well. Linear associations were studied using logistic regression analysis and odds ratios presented for the highest versus the lowest tertile of intake. In the final models, adjustments were made for maternal educational level, foreign descent, and total energy intake. Results: The intake of whole grain products and of fish was inversely associated with asthma. Adjusted odds ratios for the independent associations with whole grains and fish were 0.46 (95% CI 0.19 to 1.10) and 0.34 (95% CI 0.13 to 0.85) for current asthma and 0.28 (95% CI 0.08 to 0.99) and 0.12 (95% CI 0.02 to 0.66) for atopic asthma with BHR. Similar results were observed for current wheeze and atopic wheeze with BHR. Intake of (citrus) fruits, vegetables, and dairy products showed no clear associations with asthma end points. Conclusions: Our findings suggest that a high intake of whole grain products and fish may have a protective effect against asthma in children.